2000
DOI: 10.1074/jbc.m006943200
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Interaction with 14-3-3 and Raf-1, a Proposed Mechanism for Cross-talk of Two Signal Transduction Pathways

Abstract: The glucocorticoid receptor (GR) functions as a liganddependent transcription factor. In the present study we describe a specific immunoaffinity chromatography purification of GR from liver cytosol from adrenalectomized rats that may be used to identify hitherto unknown cytosolic GR interacting proteins. We have identified the ubiquitously expressed 14-3-3 as well as Raf-1, a downstream effector of Ras, as GR co-purifying proteins. In our semi-quantitative analysis liganded/activated GR showed the strongest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 28 publications
1
39
1
Order By: Relevance
“…We speculate that classical GR is involved in TrkB/PLC-␥ signaling because RU486 blocked the inhibitory effect of DEX, and the overexpression and down-regulation of the GR influenced TrkB/PLC-␥ signaling. Raf-1 and 14-3-3 interact with liganded-or nonliganded GR (32), implying that the GR directly influences signaling pathways in cytosol. Moreover, the GR affects the plasma membrane receptor in immune T-cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that classical GR is involved in TrkB/PLC-␥ signaling because RU486 blocked the inhibitory effect of DEX, and the overexpression and down-regulation of the GR influenced TrkB/PLC-␥ signaling. Raf-1 and 14-3-3 interact with liganded-or nonliganded GR (32), implying that the GR directly influences signaling pathways in cytosol. Moreover, the GR affects the plasma membrane receptor in immune T-cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…The cytosolic nonliganded GR is a part of a multiprotein complex in which, among other proteins, two molecules of heat shock protein 90 (hsp90), as well as one molecule each of hsp70 and hsp56 are known to be included. Widen et al 38 identified that Raf-1 copurified with GR with 14-3-3 proteins by immunoaffinity chromatography purification from liver cytosol. Interestingly, hsp90 has been shown to mediate intercellular signal transduction events including B-Raf-mediated activation of mitogen-activated protein kinase cascade by nerve growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…57 The corticosteroid receptor and Raf-1, a downstream effector of the signaling factor Ras, are found in a protein complex (the`receptosome'), providing an opportunity for the corticosteroid receptor to crosstalk with the Raf-Ras signaling pathway. 58 These interactions may be involved in regulation of cell proliferation, and induction of cell death by corticosteroids, although experimental evidence to support this concept is presently lacking.…”
Section: Signaling Pathway Crosstalkmentioning
confidence: 99%